Prognostic value of metastatic lymph node ratio and its effect on disease-free survival in colon cancer - Aslan, Orhan; Topcu, Ramazan; Sezikli, İsmail; Yüksek, Mahmut A.; Perçem, Aşkın K.; Uğur, Furkan (Frontiers in Oncology, 2025)
IntroductionThe metastatic lymph node ratio (MLNR) has been proposed as a meaningful prognostic indicator in colon cancer (CC). This study aimed to assess the prognostic relevance of MLNR by investigating its association with disease-free survival (DFS), overall survival (OS), and recurrence, and to compare its predictive value with traditional parameters, including the TNM classification and total lymph node count (TNLC).Materials and methodsThis retrospective, single-center study included patients who underwent surgical resection for colon cancer. Survival outcomes were analyzed using Kaplan-Meier survival curves and multivariate logistic regression. MLNR was evaluated in relation to demographic and clinical factors, including age, tumor location, surgical type, and the administration of adjuvant chemotherapy. The optimal MLNR cut-off value for predicting recurrence was determined via receiver operating characteristic (ROC) curve analysis.ResultsA total of 122 patients were analyzed. MLNR >0.125 was significantly associated with increased recurrence risk (adjusted HR: 7.0, p<0.001) and reduced DFS. Patients with an MLNR ≤0.125 demonstrated significantly longer DFS (p<0.001). MLNR emerged as an independent prognostic factor, offering potential prognostic benefit compared to TNLC in predicting both DFS and OS. Additionally, adjuvant chemotherapy was independently associated with a lower recurrence risk (Exp(B):0.234, p=0.038). Emergency surgery was found to be significantly correlated with poorer survival outcomes (p=0.023).ConclusionMLNR contributes additional prognostic information to the TNM staging system and may support more individualized risk stratification and decision-making regarding adjuvant therapy in colon cancer. Further large-scale prospective studies are warranted to validate these findings and to establish a clinically applicable MLNR threshold.